Welfare, happiness, and ethics - Sumner, L.W (Oxford University Press, 1996)
Moral philosophers agree that welfare matters. But they disagree about what it is, or how much it matters. Wayne Sumner presents an original theory of welfare, investigating its nature and discussing its importance. He considers and rejects all notable theories of welfare, both objective and subjective, including hedonism and theories founded on desire or preference. His own theory connects welfare closely with happiness or life satisfaction. Reacting against the value pluralism that currently dominates moral philosophy, he advances welfare as the only basic ethical value. He concludes by discussing the implications of this thesis for ethical and political theory. Written in clear, non-technical language, and including a definitive survey of other work in this area, Sumner's book is essential reading for moral philosophers, political theorists, and welfare economists.